Addressing Differentiation in Live Human Keratinocytes by Assessment of Membrane Packing Order - Gutowska-Owsiak, Danuta; Podobas, Ewa I.; Eggeling, Christian; Ogg, Graham S.; Bernardino de la Serna, Jorge (Frontiers in Cell and Developmental Biology, 2020)
Differentiation of keratinocytes is critical for epidermal stratification and formation of a protective stratum corneum. It involves a series of complex processes leading through gradual changes in characteristics and functions of keratinocytes up to their programmed cell death via cornification. The stratum corneum is a relatively impermeable barrier, comprised of dead cell remnants (corneocytes) embedded in lipid matrix. Corneocyte membranes are comprised of specialized lipids linked to late differentiation proteins, contributing to the formation of a stiff and mechanically strengthened layer. To date, the assessment of the progression of keratinocyte differentiation is only possible through determination of specific differentiation markers, e.g., by using proteomics-based approaches. Unfortunately, this requires fixation or cell lysis, and currently there is no robust methodology available to study keratinocyte differentiation in living cells in real-time. Here, we explore new live-cell based approaches for screening differentiation advancement in keratinocytes, in a “calcium switch” model. We employ a polarity-sensitive dye, Laurdan, and Laurdan general polarization function (GP) as a reporter of the degree of membrane lateral packing order or condensation, as an adequate marker of differentiation. We show that the assay is straightforward and can be conducted either on a single cell level using confocal spectral imaging or on the ensemble level using a fluorescence plate reader. Such systematic quantification may become useful for understanding mechanisms of keratinocyte differentiation, such as the role of membrane in homogeneities in stiffness, and for future therapeutic development.